Determination of Flow Accelerated Corrosion (FAC) in Feeder Pipes Using CFDd Software Fluent - Dheya Al-Othmany (Techniques and Innovation in Engineering Research Vol. 1, 2022)
Flow Accelerated Corrosion (FAC) is a corrosion mechanism caused by a combination of physical, chemical, and hydrodynamic factors, resulting in piping wall thinning. This phenomenon requires prediction and modelling to account for local and non-uniform distribution flow and mass transport characteristics. This is possible with the CFD software FLUENT. A feeder wall thing rate of 0.1084 mm/EFPY has been reported in a number of nuclear reactors. The focus of this study is on two objectives. The first was to conduct CFD analysis with FLUENT. A typical reactor’s feeder channel was modelled because it displayed a maximum wall thinning rate of 1.1 mm per year. However, the chemical treatment of the working fluid was not taken into account in this investigation. To ascertain the FAC threshold temperature, experimental tests of FAC were conducted at a range of temperatures. For water temperatures up to 90°C, no significant FAC was discovered due to experimental constraints.